Association of Pituitary Hormones and Anthropometric Parameters in Obese Infertile Women - Aslam, Farheen (International Journal of Pathology, 2021)
Introduction: World Health Organization (WHO) has acknowledged infertility as a public health problem because it challenges medical, economic and psychosocial aspects of society. Obesity has a definite impact on ovulatory function that can result in menstrual abnormalities, recurrent miscarriage and infertility. The objective of this study was to compare hormone and anthropometric parameters between primary and secondary obese infertile women and to appraise any association between these two indices in primary and secondary obese infertile females. Material and Method: This cross sectional study was carried out from January 2020 to December 2020 in infertility clinic of Bahawal Victoria Hospital. Out of 135 obese females, 90 were included in this study and secondary infertility was found in 57 of females while 33 had primary infertility. Serum FSH, LH, LH/FSH and prolactin were measured on day 3rd of menstrual cycle and BMI, waist and hip circumferences and Waist to hip ratio was calculated in both groups. Results: Serum prolactin and LH/FSH ratio was statistically raised in obese secondary infertile group. In both groups, serum FSH and central obesity indices comprising of waist circumference and waist hip ratio exhibited significant positive association. In primary infertility, serum FSH demonstrated positive association with BMI and hip circumference while in secondary infertile women, prolactin level and BMI manifested positive association. Conclusion: There was a link between hormonal derangement and obesity indices that can lead to infertility. Hence weight reduction should be considered important part of infertility treatment.